RISK LEVEL OF FISH TRANSPORTATION MODES FROM PANGGANG ISLAND TO MUARA ANGKE MARKET - Annisa Mutiarani; Fis Purwangka; Budhi Hascaryo Iskandar; Furqan (Department of Fisheries Resources Utilization, Faculty of Fisheries and Marine Science, IPB University, Bogor, Indonesia, 2026)
Fish transportation requires adequate transportation modes to ensure that fish transport activities run smoothly, yet every mode carries inherent risk. This study aimed to determine the risk level of fish transportation modes during the transport of fish from Panggang Island to Muara Angke Market. The research was conducted in March-April 2023 using a case-study method with a purposive sampling approach involving 15 respondents: fishermen, middlemen, porters, a crew member, a driver, and traders. Data were collected through direct observation and structured interviews. Risk assessment applied a semi-quantitative analysis based on the Fine (1971) method, calculating probability, exposure, and consequences. Seven fish transport modes were identified: baskets, cool boxes, wooden carts, passenger boats, pick-up trucks, cart wheel, and fibre tubs. Of 40 activity steps assessed across seven stages, 32 had an identified hazard and 8 had none; overall, 39 steps (97.5%) were acceptable and 1 (2.5%) substantial. The substantial risk was the boat sinking, colliding, or catching fire while sailing to Kali Adem Port (risk value 150), as the boat is a shared passenger-and-cargo vessel with no dedicated fish-carrying compartment. Among the identified hazards, human error was the dominant factor (51.4%), followed by technology (45.9%) and natural factors (2.7%). Key words: fish transportation, Panggang Island, risk level, semi-quantitative analysis